Pelatihan Pembuatan Selai Jambu Kristal Sebagai Upaya Peningkatan Pendapatan Petani Jambu Kristal di Desa Bantarsari - Amelia, Siti; Adriani, Aisyah Rahma; Gandhy, Abel; Anggraini, Desti (Unri Conference Series: Community Engagement, 2024)
Bantarsari Village, Rancabungur District, Bogor Regency is one of the centers for crystal guava cultivation in Bogor Regency, Bantarsari Village is even nicknamed the National Crystal Guava Village. Farmers in Bantarsari Village mostly sell their products in the form of fresh guava fruit. To increase farmers' income, it is necessary to process crystal guava into products with high added value. One potential processed product is jam. The aim of this training activity is to increase the understanding of crystal guava farmers in producing jam products. The methods used include the observation method, interviews with farmers to measure the success of this activity, while the training method is to provide innovative development for making jam products to the community. Therefore, the existence of a program to strengthen the capacity of student organizations (PPK Ormawa) of the Pakuan Management Student Association can help the Bantar Sari village community in producing derivative products with high added value in the form of Crystal Guava Jam Products. It is hoped that this product can become a sustainable alternative source of income for farmers in Bantarsari village. The result of the training activities was that guava farmers were able to process crystal guava into good quality jam products.